Sounding Like a No No : Queer Sounds and Eccentric Acts in the Post Soul Era - Royster, Francesca T. (Book collections on Project MUSE., 2023)
Sounding Like a No-Notraces a rebellious spirit in post-civil rights black music by focusing on a range of offbeat, eccentric, queer, or slippery performances by leading musicians influenced by the cultural changes brought about by the civil rights, black nationalist, feminist, and LGBTQ movements, who through reinvention created a repertoire of performances that have left a lasting mark on popular music. The book's innovative readings of performers including Michael Jackson, Grace Jones, Stevie Wonder, Eartha Kitt, and Meshell Ndegeocello demonstrate how embodied sound and performance became a means for creativity, transgression, and social critique, a way to reclaim imaginative and corporeal freedom from the social death of slavery and its legacy of racism, to engender new sexualities and desires, to escape the sometimes constrictive codes of respectability and uplift from within the black community, and to make space for new futures for their listeners. The book's perspective on music as a form of black corporeality and identity, creativity, and political engagement will appeal to those in African American studies, popular music studies, queer theory, and black performance studies; general readers will welcome its engaging, accessible, and sometimes playful writing style, including elements of memoir.